Hemostasis-related gene polymorphisms and their epistatic relationship in women with idiopathic infertility. Issue 6 (September 2019) - Velickovic, Jelena; Zeljic, Katarina; Todorovic, Jelena; Stamenkovic, Gorana; Stojkovic, Oliver
Abstract : N/A: A numerous factor can cause infertility, but around one of four reproductive failure cases remain unexplained and diagnosed as idiopathic infertility. In the past few decades, analysis of gene polymorphisms takes a significant place in pathogenesis of infertility. The aim of this study was to evaluate the possible role of hemostasis-related gene polymorphisms in unexplained infertility. The study includes 117 female patients with idiopathic infertility and 130 fertile women with at least one born child. Eight polymorphisms important for hemostasis ( ITGB3 1565T>C, FV 1691G>A, FII 20210G>A, MTHFR 677C>T and 1298A>C, ATIII 786G>A, PAI-1 4G/5G and ACE I/D) were genotyped by real-time PCR system. The frequencies of alleles and genotypes of examined polymorphisms were analyzed in SPSS statistical program, whereas gene interactions were identified using the GMDR software. Examination of etiological factors has shown that family history is a significant factor in assessing individual risk for infertility. The alleles and genotypes frequency of FV 1691G>A and FII 20210G>A polymorphisms were statistically different between control and patient group leading to a greater risk for infertility. The analysis of epistatic relationship between examined hemostasis-related gene polymorphisms identified more complex high-risk genotypes associated with infertility. Our results suggest that positive family history could be important predictive factor for fertility problems, pointing to the potential hereditary basis of this condition. Polymorphisms FVL and FII prothrombin are independent risk factors for idiopathic infertility, whereas multilocus interactions approach should be taken into consideration for the future research. Abstract : Supplemental Digital Content is available in the text